A Case with Spondyloenchondrodysplasia Treated with Growth Hormone - Utsumi, Takanori; Okada, Satoshi; Izawa, Kazushi; Honda, Yoshitaka; Nishimura, Gen; Nishikomori, Ryuta; Okano, Rika; Kobayashi, Masao (Frontiers in Endocrinology, 2017)
Spondyloenchondrodysplasia (SPENCD) is an autosomal recessive skeletal dysplasia caused by loss of function mutations in Acid Phosphatase 5, Tartrate Resistant (ACP5). Hypomorphic ACP5 mutations impair endochondral bone growth and create an interferon (INF) signature, which lead to distinctive spondylar and metaphyseal dysplasias, and extraskeletal morbidity, such as neurological involvement and immune dysregulation, respectively. We report an affected boy with novel ACP5 mutations, a splice-site mutation (736-2 A>C) and a nonsense mutation (R176X). He presented with postnatal short stature, which led to a diagnosis of partial growth hormone (GH) deficiency at 3 years of age. GH therapy was beneficial in accelerating his growth velocity. At 6 years of age, however, metaphyseal abnormalities of the knee attracted medical attention, and subsequent assessment ascertained the typical skeletal phenotype of SPENCD, brain calcifications, and an INF signature. This anecdotal experience indicates the potential efficacy of GH for growth failure in SPENCD.